A Note on the Names of Selected Magicians. (March 2015) - Nuessel, Frank
<x content-type="archive" xml:space="preserve">Abstract</x> This note defines the concept of "magic" and comments on the meaning of its various synonyms. Second, it suggests a typology of names based on 150 selected stage names or pseudonyms employed by magicians. Finally, it contains an appendix with a selected list of magicians' stage names and real names including birth and death dates (where available) and place of birth (where available).